Examining the Influence of Permissive Parenting on Student Motivation for Learning - Nisrofah, Siti (Tadibia Islamika: Journal of Holistic Islamic Education, 2023)
The repercussions of permissive parenting practices often elude caregivers, as they grapple with work-related demands that sometimes lead them to delegate their children's education entirely to the school. Permissive parenting, characterized by granting substantial freedom with minimal supervision, can result in children growing up with diminished motivation to learn. This issue necessitates a deeper exploration through literature review to shed light on the extent of the impact of permissive parenting practices on children's motivation for learning. This research adopts a qualitative approach, employing a case study research design, and draws on insights from teachers, students, and student guardians at SDN 08 Purwoharjo. Data collection methods involve observation and interviews, while analysis encompasses three stages: data reduction, presentation, and conclusion drawing. The findings reveal instances of permissive parenting practices among students at SDN 08 Purwoharjo, influenced by various factors including economic challenges and parental educational backgrounds. The consequence of permissive parenting manifests as diminished student motivation for learning at the school, resulting in apathy, neglect of assignments and teacher instructions, disrespect for others, social and academic adaptation difficulties, a lack of enthusiasm for learning, and weakened self-control.